Strategi Pengembangan Usaha Dengan Analisis Swot Pada Home Industry Pucuk Bambu: Penelitian Kasus UD Bambu Jaya Mandiri Kecamatan Ngoro Kabupaten Jombang - Siti Nur Qomariah; Novi Herawati (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to dissect the Business Development Strategy at UD Bambu Jaya Mandiri, a Home Industry focused on producing Bamboo Shoots, applying SWOT analysis, EFAS, IFAS, and Grand Strategy Matrix. Sample determination was carried out using the purposive method. This study relies on collecting primary data through direct observation and dialogue with the owners and employees of UD Bambu Jaya Mandiri and local officials of Ngoro Jombang Village, as well as secondary data obtained from existing references. To establish a business development strategy in the Bamboo Shoot Home Industry, internal factors with IFAS and external factors are evaluated using EFAS, accompanied by SWOT matrix analysis and Grand Strategy Matrix. Based on the SWOT analysis that examines internal and external factors, the Bamboo Shoot home industry is placed in quadrant 1. This indicates a very advantageous strategic position oriented towards an aggressive growth strategy.